Moving beyond expectations: From cohort-component to microsimulation projections - Zhiyang Jia; Stefan Leknes; Sturla Andreas Løkken (Statistics Norway, Research Department, 2023)
Population projections are predominantly made using the cohort-component method (CCM). The opportunities for further development within that framework are limited. Lately, with advances in technical and computational capacity, the microsimulation framework has become a serious contender. In contrast to CCM, it allows for rich com-plexity of behavior and provides insights on projection uncertainty. Still, demographers have been reluctant to apply this framework, which may be due to lack of guidance. We contribute by clarifying underlying CCM assumptions, translating a multi-regional version of the model into a dynamic spatial microsimulation model, and discuss the usefulness of prediction intervals for planning. Using data for Norway, we demonstrate that the re-sults for the two models are equivalent, even for very small subgroups, and converge with relatively few simulations. The model can easily be amended with additional indi-vidual heterogeneity, facilitating more accurate representations of population dynamics.
Keywords: J11; C15; C63; C81; 330; Population projections; microsimulation; cohort-component method; uncertainty; multi-regional; small area